x+6+2x-3=90+45

Simple and best practice solution for x+6+2x-3=90+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6+2x-3=90+45 equation:


Simplifying
x + 6 + 2x + -3 = 90 + 45

Reorder the terms:
6 + -3 + x + 2x = 90 + 45

Combine like terms: 6 + -3 = 3
3 + x + 2x = 90 + 45

Combine like terms: x + 2x = 3x
3 + 3x = 90 + 45

Combine like terms: 90 + 45 = 135
3 + 3x = 135

Solving
3 + 3x = 135

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 3x = 135 + -3

Combine like terms: 3 + -3 = 0
0 + 3x = 135 + -3
3x = 135 + -3

Combine like terms: 135 + -3 = 132
3x = 132

Divide each side by '3'.
x = 44

Simplifying
x = 44

See similar equations:

| 24x^2y^3+36x^4-72x^3y^2=0 | | 22y+18-15y= | | 5(3z-1)-2(z+2)=8(z+1) | | 4n+7-2n=3n-3 | | 60x=50(x+1) | | 2x^2-16x=7 | | 24y= | | x^2-7xy+6y^2=equation | | 2x^2+12x=12 | | 12x-5=3x+45 | | 180-x=279 | | 180-x=179 | | 160-x=88 | | ln(x)=0.0023 | | 8p^3-343/9 | | 6xwhat=96 | | 4x^2-1x-6=0 | | (1+x^4)dy+x(4y^2+1)dx=0 | | 646.8+-1.2y= | | 5.76X^2+2.86X-1.35=8 | | 10+y=10+0.5y | | 7m^2-4m=3m*(m-7/2) | | 3m*(m-7/2) | | 6x-sqrtx=12 | | 4/5x-10=54 | | f(x)=[x-3] | | 91+19m=376 | | 15x+45x-4y= | | 34n-104=338 | | 6m+6.75=63.75 | | 5x^2-6x=4x^2+6x-13 | | 2a+2x+x=70 |

Equations solver categories